Determinants of trade balance in Southeast Asian countries / Wan Syahira Illyana Wan Shahrul Bahrin and Bee-Hoong Tay - Wan Shahrul Bahrin, Wan Syahira Illyana; Bee-Hoong, Tay (Universiti Teknologi MARA, Kedah, 2023)
This study aims to examine the macroeconomic stability in determining the trade balance performance in Southeast Asian countries. Using a panel data analysis in the period of 2005 to 2020, this study analyses whether gross domestic product, energy consumption, domestic consumption expenditure, foreign direct investment and exchange rate affect trade balance based on the method of pooled ordinary least squares in Malaysia, Thailand, Singapore, Philippines, and Indonesia. Results of the study demonstrates that energy consumption and foreign direct investment positively affected trade balance. A country's energy demand may be positively impacted by increased energy use, especially for renewable energy, which may help the trade balance by lowering imports of other energy sources. As FDI flow increases, international companies are encouraged to create domestic import substitution, resulting in lower imports and a favourable influence on the trade balance. The prime factor that has a significant negative impact on trade balance is domestic consumption expenditure. Consumption expenditures have an inverse relationship with the trade balance since they might rise along with household income, especially when it comes to imports. This study contributes by providing significant information to help the authority to identify measures to be taken to improve the trade balance performance. To enhance the study's findings, it is recommended that future research use more sophisticated techniques, such as the ARDL or nonlinear ARDL model. Future research may also consider a longer period of observation, including the COVID-19 period, as well as other variables that are important in explaining trade balance.